Founders’ Creativity, Business Model Innovation, and Business Growth - Li, Yang; Li, Beiwei; Lu, Tianhao (Frontiers in Psychology, 2022)
Given the existing studies on the role of different founders’ personalities in the growth of new ventures, we take the digital technology start-ups as the research object and focus on the role of founders’ creativity. In this study, we assess the relationship between founders’ creativity and business growth. According to the framework of upper echelons theory, we propose several hypotheses. Based on the investigation of 153 new ventures in China’s transition economy, we find that: (1) founders’ creativity has a positive impact on the growth of enterprises; (2) business model innovation positively mediates the relationship between founders’ creativity and enterprise growth; (3) work experience is found to be a moderator of the relationship between founders’ creativity and business model innovation. The conclusion of our analysis not only helps to further deepen the research on the growth process of start-ups but also helps to further expand the important role of business model innovation and founders’ work experience in the growth of new firms.